Research progress on pathogenesis and treatment of Rasmussen encephalitis - WU Hong⁃mei; JI Tao⁃yun; ZHUANG Ji⁃xin (Chinese Journal of Contemporary Neurology and Neurosurgery)
The pathogenesis of Rasmussen encephalitis (RE) remains unclear. Current theories suggest that viral infection, antibody⁃mediated humoral immune mechanisms, T lymphocytes mediated cellular immunity, and microglia mediated neurodegeneration may all be involved in disease onset and progression. In the early stage of disease, immunotherapy targeting induced by T lymphocytes and microglia could slow down disease progression of some patients. This review summarizes the latest research on the main pathogenic hypotheses and treatment strategies for RE, aiming to enhance clinical understanding of the disease and provide guidance for therapeutic interventions.